General Merchandising LLC’s colleagues' perceptions of the JMPT program and its effectiveness: the case on how to produce effective leaders - Davis, Travis (Kansas State University, 2013)
Companies use various methods to prepare their new management recruits to take on and succeed in their jobs. Some are formal, but most involve some form of informal arrangements such as mentorship. This mentorship approach is used by General Merchandising LLC as the principal preparation program for its new management recruits. This program is the Junior Management Trainee Program (JMTP). Apart from building the management capacity of its new managers, the JMTP aims to ensure that the management procedures and managerial skills at all the elevator and terminal locations across the organization are standardized, such that transferring individual across the organization is smooth and demands little or no learning of general operations and procedures. The JMTP has been ongoing for a fifteen years and has, generally, produced excellent results. The factors that contribute to its performance, however, have never been studied. This research seeks to understand the factors that contributed to the success of the program, with the view to streamlining the management and operation of the JMTP. The study was conducted using primary data collected from current participants in the JMTP and people who have served as mentors to new management recruits over the past three years. The survey was on the population of all people in the company who fit the foregoing description. The survey instrument was a structured questionnaire delivered electronically using Axio™, a survey software operated by Kansas State University. The data was analyzed using Stata® 12.0. The effectiveness of the JMTP was determined through an assessment of graduates’ ability to effectively operate their own grain terminal facility upon graduation. The factors considered as explanatory variables for peoples’ responses to this included their current role – whether they were management trainee or a mentor – and their demographic characteristics, as well as their perceived relationship with their mentors or mentees. The learning style of individual mentees was also determined to influence perceptions about the effectiveness of the current program in preparing them to independently run a terminal facility. The results suggest that personality types and learning styles should be taken into consideration and used when recruiting trainee managers and assigning them in order to maximize the effectiveness of the JMTP. It is additionally important that improvements and/or changes in the program be organized in ways that accommodate the different needs of both mentees and mentors in order to achieve high capacity improvement as a result of the training program. The study results specifically point to a sequence of initiatives that may be employed to enhance the outcomes of the JMTP: 1. Implement a psychometric questionnaire for mentors and incoming JMTPs to ensure maximum compatibility between mentors and mentee to enhance learning and capacity development. 2. Use the results from this study to initiate a process of collecting relevant data on performance of new managers and the training program itself on a regular basis to ensure the continuous improvement in the JMTP. 3. Use the results to develop mentorship education programs for the company’s mentors to help mentors do a better job to enhance new managers’ performance.
Keywords: Management; Leadership; Organizational performance; Training; Perception